Ein Compendium sumerisch-akkadischer Beschwörungen - Schramm, Wolfgang (Universitätsverlag Göttingen, 2008)
The magic way of thinking and acting belongs to the conspicuous characteristics of the old oriental culture. Threats to mankind, especially diseases, are induced by demons. But these diseases can be avert with the help of the god Enki (Ea) and his son Asalluhi (Marduk). The present collection of 21 spells is a profile through the ritual practice of the cleaning of ill people. The texts are based primarily on manuscripts from the library of Assurbanipal in Ninive (7th century b.c.) . But the some spells are from earlier transcriptions of the 2nd century b.c. A lot of the material in this book is published for the first time. So, this book contributes for the reconstruction of religious literature of the Old Orient.